Entrepreneurial attributes of undergraduate business students: a three country comparison revisited - Shelley Farrington; Danie Venter; Christine Schrage; Peter van der Meer (South African Journal of Economic and Management Sciences, 2012)
In 2001/2002 a study was undertaken to establish whether significant differences existed between the levels of development of several entrepreneurial attributes, as perceived by undergraduate business students from three universities in three different countries. The rationale was that, if entrepreneurial attributes could be identified as more developed in one country than in another, solutions could be provided for developing these attributes in others. The primary objective of this study is to investigate and compare the levels of development of entrepreneurial attributes of undergraduate business students in the present study (2010) to the levels of development reported by undergraduate business students in the 2001/2002 study. Cronbach alpha coefficients were calculated to assess the reliability of the measuring instrument and ttests to establish significant differences. Cohen’s d statistics were calculated to establish practical significance. The findings suggest that the educational environment and entrepreneurship education policy of the Dutch university participating in this study could provide solutions as to how entrepreneurial attributes among students could be developed further.